2018
DOI: 10.3892/etm.2018.6292
|View full text |Cite
|
Sign up to set email alerts
|

Compound Astragalus and Salvia miltiorrhiza extract inhibits hepatocarcinogenesis via modulating TGF‑β/TβR and Imp7/8

Abstract: Compound Astragalus and Salvia miltiorrhiza extract (CASE) is a Chinese herbal formula consisting of astragalosides, astragalus polysaccharide and salvianolic acids extracted from Astragalus membranaceus and Salvia miltiorhiza. Previous studies by our group have demonstrated that CASE effectively suppresses diethylinitrosamine (DEN)-induced hepatocellular carcinoma (HCC) in rats via modulating transforming growth factor β/Mothers against decapentaplegic (TGFβ/Smad) signaling. To further elucidate the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…While signaling pathway was affected by the Astragalus compound which manifests an anti-tumor effect against Hepatoma. (Wu et al 2018 ) Promoting secretions of cytokines Ganoderma lucidum showed an anti-tumor effect against H22 transplanted mice. (Chen et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…While signaling pathway was affected by the Astragalus compound which manifests an anti-tumor effect against Hepatoma. (Wu et al 2018 ) Promoting secretions of cytokines Ganoderma lucidum showed an anti-tumor effect against H22 transplanted mice. (Chen et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…APS inhibits cell proliferation and migration of Tregs by repressing the expression of FOXp3, which contributes to inhibit the immune suppressive effects of Tregs in the tumour microenvironment of HCC (Wu et al. 2018 ). However, little is known about whether APS can regulate polarization of TAMs to participate in the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al (2018) demonstrated that Sal B reversed tumor MDR by down-regulating the expression of CD44, SOX2 and ABCG2 proteins in LoVo and HCT-116 colonic CSC xenografts. A recent study by Wu et al (2018) indicated that S. miltiorrhiza extract inhibited hepatocarcinogenesis by modulating TGF-β/TβR and Imp7/8 protein expression, suggesting that S. miltiorrhiza has multiple targets in HCC treatment.…”
Section: Potential Applications Of Salvianolic Acids For the Treatmenmentioning
confidence: 99%